Separation and purification of chicken IgY with its field efficacy in controlling avian influenza in Muscovy ducks - F. M. Radwan; A. A. El-Shemy; N. I. Toaleb; M. A. Bastamy; M. M. Amer (Bulgarian Journal of Veterinary Medicine)
The study aimed to prepare pure immunoglobulin Y (IgY) and investigate its potential of use in avian influenza (AI) H5N1 control in naturally infected ducks. The IgY was prepared using the polymer precipitation method and was found to have high hemagglutination inhibition (HI) mean titres against H5, H9, and ND by the 5th and 8th week post-vaccination (wpv). The separated IgY had mean HI titres against H5 7.20±0.46 and 7.60±0.74 for 5 and 8 wpv, respectively. SDS-PAGE analysis showed the presence of two prominent bands with molecular weight 65.08 and 27.96 kDa at 5 wpv, which resolved into 65.98 and 27.96 kDa at 8 wpv. The protein concentration of IgY was 3.92 and 5.71 mg/mL at 5 and 8 wpv, respectively. The therapeutic potential of IgY was evaluated in 33-day-old Muscovy male ducks showing signs of AI H5N1 infection with 35% mortality within 36 hours. The ducks were injected intramuscularly (i.m.) with 1 mL IgY diluted 1/5 or 1/10 for three successive days. The results showed that the ducks injected with IgY had reduced mortality rates compared to the non-injected ducks. After the third injection, the ducks appeared to be normal, and the total mor-tality rate was 23.7% and 45.18% in 1/5 and 1/10 injected birds, respectively, compared to 98.08% in non-injected birds. In conclusion, the study suggests that IgY prepared from immunised hens can be used to control AI H5N1 in ducks. However, further investigations are needed to determine the accurate dose, time, and concentration of protein required for effective treatment.